Construction of a Recombinant Porcine Epidemic Diarrhea Virus Encoding Nanoluciferase for High-Throughput Screening of Natural Antiviral Products - Wan Li; Mengjia Zhang; Huijun Zheng; Peng Zhou; Zheng Liu; Anan Jongkaewwattana; Rui Luo; Qigai He (Viruses, 2021)
Porcine epidemic diarrhea virus (PEDV) is the predominant cause of an acute, highly contagious enteric disease in neonatal piglets. There are currently no approved drugs against PEDV infection. Here, we report the development of a nanoluciferase (NLuc)-based high-throughput screening (HTS) platform to identify novel anti-PEDV compounds. We constructed a full-length cDNA clone for a cell-adapted PEDV strain YN150. Using reverse genetics, we replaced the open reading frame 3 (ORF3) in the viral genome with an NLuc gene to engineer a recombinant PEDV expressing NLuc (rPEDV-NLuc). rPEDV-NLuc produced similar plaque morphology and showed similar growth kinetics compared with the wild-type PEDV in vitro. Remarkably, the level of luciferase activity could be stably detected in rPEDV-NLuc-infected cells and exhibited a strong positive correlation with the viral titers. Given that NLuc expression represents a direct readout of PEDV replication, anti-PEDV compounds could be easily identified by quantifying the NLuc activity. Using this platform, we screened for the anti-PEDV compounds from a library of 803 natural products and identified 25 compounds that could significantly inhibit PEDV replication. Interestingly, 7 of the 25 identified compounds were natural antioxidants, including Betulonic acid, Ursonic acid, esculetin, lithocholic acid, nordihydroguaiaretic acid, caffeic acid phenethyl ester, and grape seed extract. As expected, all of the antioxidants could potently reduce PEDV-induced oxygen species production, which, in turn, inhibit PEDV replication in a dose-dependent manner. Collectively, our findings provide a powerful platform for the rapid screening of promising therapeutic compounds against PEDV infection.